Developing a Simpler Prognosticating Tool: Comparing the Combined Assessment of Risk Encountered in Surgery Score with Deyo-Charlson Comorbidity Index and The American Society of Anesthesiologists Physical Status Score in Predicting 2 years Mortality after Hip Fracture Surgery. (24th September 2021) - Cher, Eric Wei Liang; Carson, John Allen; Sim, Eileen Yilin; Abdullah, Hairil Rizal; Howe, Tet Sen; Koh Suang Bee, Joyce,
Background: The use of risk stratification tools in identifying high-risk hip fracture patients plays an important role during treatment. The aim of this study was to compare our locally derived Combined Assessment of Risk Encountered in Surgery (CARES) score with the the American Society of Anesthesiologists physical status (ASA-PS) score and the Deyo–Charlson Comorbidity Index (D-CCI) in predicting 2-year mortality after hip fracture surgery.Methods and Material: A retrospective study was conducted on surgically treated hip fracture patients in a large tertiary hospital from Jan 2013 through Dec 2015. Age, gender, time to surgery, ASA-PS score, D-CCI, and CARES score were obtained. Univariate and multivariable logistic regression analyses were used to assess statistical significance of scores and risk factors, and area under the receiver operating characteristic (ROC) curve (AUC) was used to compare ASA-PS, D-CCI, and CARES as predictors of mortality at 2 years.Results: 763 surgically treated hip fracture patients were included in this study. The 2-year mortality rate was 13.1% (n = 100), and the mean ± SD CARES score of surviving and demised patients was 21.2 ± 5.98 and 25.9 ± 5.59, respectively. Using AUC, CARES was shown to be a better predictor of 2-year mortality than ASA-PS, but we found no statistical difference between CARES and D-CCI. A CARES score of 23, attributable primarily to pre-surgical morbidities and poor health of the patient, was identified as the statistical threshold for "high" risk of 2-year mortality.Conclusion: The CARES score is a viable risk predictor for 2-year mortality following hip fracture surgery and is comparable to the D-CCI in predictive capability. Our results support the use of a simpler yet clinically relevant CARES in prognosticating mortality following hip fracture surgery, particularly when information on the pre-existing comorbidities of the patient is not immediately available.